Current situation and future perspectives for the use of fungi in the biomaterial industry and proposal for a new classification of fungal-derived materials - Ballen Sierra, Luz Alba; Mendes-Pereira, Thairine; García, Glen Jasper Yupanqui; Werkhaizer, Carla Queiroga; de Rezende, Juliana B.; Rodrigues, Thiago Augusto Borges; Badotti, Fernanda; Cardoso, Emanuelle Santos de Carvalho; da Costa, Andréa Miura; Uetanabaro, Ana Paula; Aguilar, Maria Teresa; Góes-Neto, Aristóteles (PeerJ Materials Science, 2023)
The potential applications of fungi in the development of new biomaterials derived from fungal mycelium have captured the attention from both the scientific community and the society. The notable ability of mycelium networks to self-construct and aggregate can be used to produce diverse biomaterials. These biomaterials can be created in a pure state, or both in conjunction with other organic/inorganic compounds. Recent advancements in mycomaterials have gained attention due to their sustainability and mechanical, thermogravimetric, and compression properties. Such properties contribute to reducing the reliance on environmentally problematic substrates within the industry. After a standardized and comprehensive review of publications on mycomaterials across different fields, such as biology, health, agriculture, engineering, and material sciences, we detected that publications on this theme are utterly scattered. This critical review enabled us to also propose a novel classification system for these fungal-derived materials to help to structure and standardize this emerging transdisciplinary field of knowledge.
Keywords: Biological materials; Fungi; Mycelium; Mycomaterials; Bioindustry